PENGARUH INFLASI DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Nadilla Nadilla; Efral Aulia Yustian; Sri Defi Wahyuni; Nia Anggina; Adinda Tria Syalsabila; Ansofino Ansofino (STKIP Pesisir Selatan, 2026)
study aims to analyze the influence of inflation and interest rates on economic growth in Indonesia. The type of research is associative research. The data used is time series data for the period 1986–2024 sourced from the Central Statistics Agency (BPS) and the World Bank. The analytical method used is multiple linear regression, preceded by a stationarity test to ensure the validity of the data. The results show that inflation has a negative and significant effect on economic growth in Indonesia, meaning that increasing inflation tends to reduce the rate of economic growth. Meanwhile, interest rates do not have a significant effect on economic growth, although they have a very small positive coefficient. Simultaneously, inflation and interest rates are able to explain 52.5 percent of the variation in economic growth, while the remainder is influenced by other variables outside the research model. These findings indicate that inflation stability is an important factor that needs to be a primary focus in the formulation of economic policies to support sustainable economic growth in Indonesia